2017
DOI: 10.1155/2017/9428176
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Safety and Functional Efficacy of Stem Cell-Based Therapeutic Approaches Using Retinal Degenerative Animal Models

Abstract: Dysfunction and death of retinal pigment epithelium (RPE) and or photoreceptors can lead to irreversible vision loss. The eye represents an ideal microenvironment for stem cell-based therapy. It is considered an "immune privileged" site, and the number of cells needed for therapy is relatively low for the area of focused vision (macula). Further, surgical placement of stem cell-derived grafts (RPE, retinal progenitors, and photoreceptor precursors) into the vitreous cavity or subretinal space has been well est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 215 publications
(251 reference statements)
1
16
0
Order By: Relevance
“…Several approaches, such as intravenous injection, intravitreous injection and SI, have been reported that could deliver retinotoxic reagents into the animal eyes to induce RD models [13]. Each approach has its own advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several approaches, such as intravenous injection, intravitreous injection and SI, have been reported that could deliver retinotoxic reagents into the animal eyes to induce RD models [13]. Each approach has its own advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous injection was a common and easy method to damage the bilateral retina with large lesion areas in small and medium animals [26,27]. However, systemic administration of retinotoxic agents would also affect the general health status of the experimental animals, and even lead to death and tumor formation [13]. Furthermore, higher dose of retinotoxic agents for large animals like monkeys was used to induce retinal damage, which caused severe renal toxicity or death [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations